2018
DOI: 10.1016/j.mcn.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic investigation into mechanisms underpinning corticosteroid effects on neural stem cells

Abstract: Corticosteroids (CSs) are widely used clinically, for example in pediatric respiratory distress syndrome, and immunosuppression to prevent rejection of stem cell transplant populations in neural cell therapy. However, such treatment can be associated with adverse effects such as impaired neurogenesis and myelination, and increased risk of cerebral palsy. There is increasing evidence that CSs can adversely influence key biological properties of neural stem cells (NSCs) but the molecular mechanisms underpinning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The results showed that BV‐2 cells activated by CORT significantly inhibited the proliferation and differentiation of NSCs. It is worthy to note that, CORT itself exerted inhibitory effect on the proliferation and differentiation of NSCs 73‐75 . It can be inferred from the above analysis that CORT‐induced microglia activation is an adverse factor for stress‐inhibited neurogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…The results showed that BV‐2 cells activated by CORT significantly inhibited the proliferation and differentiation of NSCs. It is worthy to note that, CORT itself exerted inhibitory effect on the proliferation and differentiation of NSCs 73‐75 . It can be inferred from the above analysis that CORT‐induced microglia activation is an adverse factor for stress‐inhibited neurogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…Hematopoietic stem cells have self-renewal and multi-lineage differentiation properties, but larger studies need to be conducted in order to confirm these results [25]. Neural stem cells generate the major cell types found within the CNS (astrocytes, oligodendrocytes, and neurons), playing a key role in brain development [60]. However, collecting these cells from the brain or spinal cord is not easily accessible.…”
Section: Resultsmentioning
confidence: 99%
“…NSCs can synthesize glia secreting substances, which have anticonvulsant qualities, as well as GABA neurotransmitters [38]. NSCs are multipotent and believed to be capable of generating the major cell types of the CNS (astrocytes, neurons, and oligodendrocytes) [39]. In the adult brain neurogenesis is only located within two regions -the subventricular zone of the lateral ventricle and the subgranular zone of the hippocampus [40].…”
Section: Neural Stem Cellsmentioning
confidence: 99%